Radar sea clutter : modelling and target detection - Rosenberg, Luke; Watts, Simon, 1949- (Institution of Engineering & Technology, 2022)
This book presents comprehensive coverage of new research into sea clutter characterisation and modelling, radar performance prediction and maritime target detection. The book also includes a summary of sea-clutter scattering characteristics and datasets provided that can be used for modelling.
Keywords: Incoherent scatter radar.; Incoherent scatter radar -- Mathematical models.; Radar -- Interference.; Radar -- Interference -- Mathematical models.; Radar in navigation.; Radar in navigation -- Mathematical models.; elektronické knihy; electronic books